Pulmonary alveolar proteinosis with an unusual bronchoscopic complication. Issue 11 (4th October 2021) - Sweeney, Duncan J.; Munsif, Maitri; Pilcher, David; Stirling, Rob G.; Leong, Tracy L.
Abstract: Pulmonary alveolar proteinosis (PAP) is a rare respiratory syndrome, which can be challenging to diagnose given its non‐specific presentation and imaging findings. While most primary cases of PAP have an autoimmune basis, the triggers for the disease are uncertain with occupational factors increasingly thought to be important. We report the unusual complication of pneumomediastinum and bilateral pneumothoraces following endobronchial ultrasound‐guided transbronchial needle aspirate in the setting of PAP. We discuss the possible physiological mechanisms of this complication, which appears to be more common in conditions with reduced lung compliance. Abstract : Pulmonary alveolar proteinosis is a rare disease which can be challenging to diagnose. We report the case of a 30‐year‐old male who developed the condition in the setting of occupational exposures and describe an unusual complication of bronchoscopy that presented management challenges.